أثر خصائص أعضاء مجلس الإدارة على الإفصاح عن المخاطر في الشركات المساهمة العامة الصناعية المدرجة في بورصة عمان - الرباع، حسين محمد; المحاميد، طارق رفاعي (الجامعة الأردنية - عمادة البحث العلمي, 2020)
هدفت الدراسة إلى معرفة أثر خصائص أعضاء مجلس الإدارة على الإفصاح عن المخاطر في الشركات المساهمة العامة الصناعية المدرجة في بورصة عمان، واستقصاء علاقة كل من: حجم الشركة، وجودة التدقيق، وربحية الشركة، والرفع المالي بالإفصاح عن المخاطر. تم استخدام عينة مكونة من 48 شركة من أصل 50 من الشركات الصناعية المدرجة في بورصة عمان في الفترة (2012-2017). بينت نتائج الدراسة أن هناك أثراً لخصائص مجلس الإدارة على الإفصاح عن المخاطر؛ فقد لوحظ وجود علاقة عكسية غير مهمة إحصائياً بين نسبة ملكية مجلس الإدارة والإفصاح عن المخاطر للفترة (2012-2017)، وتوصلت الدراسة إلى عدم وجود علاقة ذات دلالة إحصائية بين كل من: استقلالية مجلس الإدارة، وحوافز مجلس الإدارة، والفصل بين رئيس مجلس الإدارة والمدير التنفيذي، وبين الإفصاح عن المخاطر في الشركات الصناعية المدرجة في بورصة عمان للفترة (2012-2017). بناء على النتائج، فإن الدراسة توصي بضرورة توعية مستخدمي التقارير المالية بنتائج وانعكاسات الإفصاح عن المخاطر على قراراتهم الاستثمارية، وبدعوة إدارات الشركات الصناعية الأردنية لتكثيف الجهود مع الأطراف ذات العلاقة، متمثلة بهيئة الأوراق المالية، وبورصة عمان، والهيئات التشريعية، والمساهمين، والعملاء، والمدققين، والمحللين الماليين، للتوصل إلى قوائم مالية تتصف بالعرض الكافي والواضح للمخاطر التي تتعرض لها الشركات الصناعية. كما توصي الدراسة بالتوسع بالبحث في أثر الإفصاح عن المخاطر في القطاعات الاقتصادية الأخرى، لمعرفة ما إذا كانت خصائص مجلس الإدارة تسهم في زيادة أو تخفيض الإفصاحات عن المخاطر.
This study aims to identify the impact of the traits of the members of the board of directors on risk disclosure in industrial corporations listed in the Amman Stock Exchange (ASE). It also aims to explore the impact of company size, audit quality, the profitability of the company and the financial leverage on risk disclosure. A sample of 48 industrial companies listed in ASE during the period from 2012 to 2017 as well as the index of mandatory risk disclosure were used to find out whether companies disclosed risks or not. Data was analyzed and descriptive analysis of the study’s variables as well as the variance inflation factor (VIF) test and multiple regression analysis were used to test the hypotheses. The results of the study showed that the board of directors’ traits had a significant impact on risk disclosure. A statistically significant inverse relationship was observed between the board of directors' ownership and risk disclosure. The results showed no statistically significant proportionality between the size of the board of directors and risk disclosure in industrial companies listed in ASE between 2012 and 2017. Moreover, the results showed no statistically significant relationship between the board of directors’ independence and incentives as well as separating the chairman and the CEO while disclosing risks in industrial companies listed in ASE between 2012 and 2017. The study recommends that users of financial reports should be made aware of the results and implications of risk disclosure on their investment decisions .It also recommends that administrations of Jordanian industrial companies intensify their efforts in cooperation with relevant parties, represented by the Securities Commission, ASE legislative bodies, shareholders, clients, auditors and financial analysts in order to create financial statements that adequately and clearly demonstrate the risks faced by industrial companies. In addition to that, the study recommends expanding research on the impact of risk disclosure to other economic sectors in order to determine whether the traits of the board of directors contribute to increasing or reducing risk disclosures.
Keywords: المحاسبة -- مجلس الإدارة -- الإفصاح عن المخاطر -- الشركات الصناعية الأردنية -- بورصة عمان